2001
DOI: 10.1258/1357633011937344
|View full text |Cite
|
Sign up to set email alerts
|

Taking telehealth to the bush: Lessons from north Queensland

Abstract: Networking North Queensland (NNQ) was a two-year project to improve access to health services in rural and remote communities. The project involved email and Internet access in 61 communities, in a region almost three times the size of the UK. Videoconferencing equipment was also installed at 21 sites and a total of 197 h of videoconferencing was recorded at 10 of the remote sites over 12 months. As a result of the project, health consumers enjoyed improved access to medical, specialist, allied health and prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…Second, in line with previous research, a number of inter-personal and operational factors were identified as key enablers. 14,16 Conditions such as positive working relationships and ensuring clinical buy-in were identified as important for sustaining engagement with telehealth, which agrees with findings reported by Wade and Eliott 17 who argued that telehealth requires the development of relationships between clinicians. Logistical and practical factors associated with the introduction of telehealth suggest that telehealth systems should adapt and link in to the day to day operations of the practice and not vice versa.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Second, in line with previous research, a number of inter-personal and operational factors were identified as key enablers. 14,16 Conditions such as positive working relationships and ensuring clinical buy-in were identified as important for sustaining engagement with telehealth, which agrees with findings reported by Wade and Eliott 17 who argued that telehealth requires the development of relationships between clinicians. Logistical and practical factors associated with the introduction of telehealth suggest that telehealth systems should adapt and link in to the day to day operations of the practice and not vice versa.…”
Section: Discussionsupporting
confidence: 85%
“…12 Research has also identified the lack of appropriate equipment, poor technology infrastructure and unreliable internet access particularly outside metropolitan areas as affecting the extensive use of telehealth. 13,14…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported in a recent literature review [24], problems related to nonverbal communication and audiovisual quality are seen as drawbacks to telepsychiatry and that more needs to be done to improve infrastructure issues [19]. Also, training, ongoing technical support [25], and more user-friendly technology [26] have been shown to facilitate acceptance. Comfort levels could also be improved through better communication and information exchange, for example, providing consultants with information regarding available resources in local communities as well as postconsultation feedback regarding the appropriateness and usefulness of their recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…This study did not collect information about the types of communications technology used in telehealth activities or the nature, purpose or frequency of those activities. The ANZTC survey, although becoming outdated, provides a broad overview 4 , and details of the development and implementation of telehealth in the state of Queensland have been provided elsewhere [8][9][10] . However, our results do provide a picture of where telehealth is being currently used in Australia, at least in the hospital context.…”
mentioning
confidence: 99%